MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI PENGGUNAAN STRATEGI PEMBELAJARAN INDEX CARD MATCH DALAM PEMBELAJARAN IPS KELAS VIII B SMP NEGERI 2 SAWIT BOYOLALI - Djumali, Djumali (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2013)
Learning is very important for the students, the colourful of learning is absolutely dependson teachers. Whether the students will be motivated for learning actively or not, dependson how much teachers used actively learning process in classroom. The usage of learningIndex Card Match strategy can motivate students’ study so that influence students’ participationin IPS learning for increasing students’ study achievement.The research result from this classroomaction research showed that by using learning Index Card Match strategy can increase students’study motivation with indicator the level students active participation in learning increasedand evaluation result of students can achieve the average of class KKM that is established,(KKM = 63).